2022
DOI: 10.1182/blood.2021015341
|View full text |Cite
|
Sign up to set email alerts
|

Combining nilotinib and PD-L1 blockade reverses CD4+ T-cell dysfunction and prevents relapse in acute B-cell leukemia

Abstract: Patients with acute lymphoblastic leukemia have experienced significantly improved outcomes due to the advent of chimeric antigen receptor T-cells and bispecific T-cell engagers, although a proportion of patients still relapse despite these advances. T-cell exhaustion has been recently suggested to be an important driver of relapse in these patients. Indeed, phenotypic exhaustion of CD4+ T-cells is predictive of relapse and poor overall survival in B-ALL. Thus, therapies that counter T-cell exhaustion, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Consistent with previous reports, patients in cluster 2 with a high TMB (>10 Mb) and low TIDE score had a better response to PD-1/PD-L1 blockade therapy (Figures 4G-J) (Chan et al, 2019). In addition, the low-risk group was more susceptible to ipifarnib and nilotinib, both of which inhibit PD-1/PD-L1 directly or indirectly (Jackson et al, 1986;Tracy et al, 2022). Altogether, our results confirmed that TPCs are a valuable tool for predicting drug sensitivity and immunotherapy responses in patients with LUAD.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous reports, patients in cluster 2 with a high TMB (>10 Mb) and low TIDE score had a better response to PD-1/PD-L1 blockade therapy (Figures 4G-J) (Chan et al, 2019). In addition, the low-risk group was more susceptible to ipifarnib and nilotinib, both of which inhibit PD-1/PD-L1 directly or indirectly (Jackson et al, 1986;Tracy et al, 2022). Altogether, our results confirmed that TPCs are a valuable tool for predicting drug sensitivity and immunotherapy responses in patients with LUAD.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, the small‐molecule inhibitor of ABL named GNF‐2 overcomes off‐target toxicities in solid malignancies, improving clinical efficacy 31 . Combining anti‐PD‐L1 drug and nilotinib, a tyrosine kinase inhibitor targeting BCR‐ABL, markedly increases survival of leukemic mice 32 . These potential drugs and targeted pathways brought a new direction for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Combining anti‐PD‐L1 drug and nilotinib, a tyrosine kinase inhibitor targeting BCR‐ABL, markedly increases survival of leukemic mice. 32 These potential drugs and targeted pathways brought a new direction for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PD-L1 antibodies can also block the binding of PD-L1 to PD-1, thereby inhibiting the exhaustion of T cells. Combination therapy with anti-PD-L1 and the tyrosine kinase inhibitor nilotinib can reduce T-cell exhaustion markers in leukemia and significantly improve the long-term survival rate of mice with leukemia ( 189 ). Anti-PD-1 and anti-PD-L1 therapies can reduce T-cell exhaustion and achieve superior treatment outcomes.…”
Section: Targeting T-cell Exhaustion and T Scm To ...mentioning
confidence: 99%